Analisis Biomekanika Keterampilan Servis Atas Floating Bolavoli pada Pemain Putri - ANDANI, LINA FARDA; Sulaiman, Sulaiman (Indonesian Journal for Physical Education and Sport, 2023)
The focus of this research is to analyze the biomechanics of floating serve skills in female players and to analyze the correct technique of floating volleyball serve. Researchers used quantitative research methods with a descriptive approach. Data generated from video capture and analyzed using software kinovea series 0.8.15. The population in this study were female volleyball players with a total sample of 8 athletes. In the initial phase, the correct technique forms an angle of 140º and the right foot behind forms a 160º angle, the left hand holding the ball is used to bounce the ball up to form an angle of 101º, and a step of 90.82 cm, while the right hand is above the back of the head. In the execution phase the ball is thrown up, swing your right hand back until your back leans back to form an angle of 138º, then punch using your right hand to form an angle of 156º. In the continuation phase after hitting, the batting arm is parallel to the body force line which is pushed forward in order to get balance and the left leg bends slightly to form an angle of 144º. The results of the research that has been carried out can be concluded that the correct floating volleyball service movement has three phases, namely: the initial phase, the implementation phase, and the continuation phase.